Advancing the constitutional goal of social justice through a teleological interpretation of key concepts in the environmental rights in section 24 - Donald, Megan Elizabeth (Stellenbosch : Stellenbosch University, 2015)
Thesis (LLM)--Stellenbosch University, 2014.